Pelatihan Pengembangan Unit Usaha Koperasi Pegawai Negeri Angkasa RRI: Strategi dan Tantangan - Risnawati, Nanik (E-Coops-Day, 2024)
The Angkasa RRI Civil Servant Cooperative is an employee cooperative whose members are employees of Radio Republik Indonesia in the Special Region of Yogyakarta. Currently, the cooperative only has one business unit, namely the savings and loans unit. As a form of effort to continue trying to improve the welfare of its members, the administrators of the Angkasa RRI Civil Servant Cooperative intend to carry out business development by providing services to both members and non-members. Therefore, training was carried out for administrators, supervisors, and members and involved students from the Indonesian Cooperative University (Ikopin University) who were carrying out Field Practices. On this occasion, the training participants seemed enthusiastic about participating in the training. And it was conveyed that to carry out business development there are several strategic options that can be used by the Angkasa RRI Civil Servant Cooperative. These include a differentiation strategy, a cheaper price strategy than competitors, a focus strategy, a diversification strategy, and an integration strategy. In designing business development, new businesses must remain a priority for members. However, it is still permissible to serve non-members as long as the members are served well and feel satisfied. The steps that need to be prepared in planning business development are evaluating the current cooperative business situation using SWOT analysis, setting business development goals, identifying opportunities and challenges, identifying competitors and target markets, developing business plans, financing and budgeting, and introducing risks, development team, implementation schedule, performance evaluation and measurement, Stakeholder Communication and Engagement, Monitoring, and adjustments. By applying These steps will carefully help the Angkasa RRI civil servant cooperative to plan business development more effectively and increase the chances of success in achieving its business goals.